Cleopatra - Daynes, Katie; Riglietti, Serena (Usborne London, 2004)
In the land of Pharoahs and pyramids, Cleopatra is a princess with an uncertain future. When own brother tries to kill her, she realises she can't trust anyone. Then Rome's leaders start vying for her attention and Cleopatra faces her greatest challenge yet